Preparation of a board game as a teaching practice in teaching and learning adolescentes about HPV in a border municipality (Research, Society and Development, 2024)
The human papilloma virus, better known as HPV, is currently one of the most sexually spread diseases, and is also strongly related to the development of several types of cancer, including cervical cancer. In this sense, the present research aims to: Raise awareness among elementary school students about the infection caused by HPV in a public school in the municipality of Guajará-Mirim/RO on the border with Bolivia. Materials and methods: bibliographic analysis of scientific articles; application of a semi-structured questionnaire with the aim of ascertaining students’ prior knowledge about HPV; pedagogical intervention with the construction of a board game developed jointly by the researcher and students. Results and Discussion: the proposed activities promoted student involvement in the topic, promoting learning mainly in relation to the means of transmission of STIs. Results: health actions are important in the school environment, especially to clarify students' main doubts regarding STIs.